Microlithic Sites of Mandla (Madhya Pradesh: India) and the Problem of Schematic Generalisation in Prehistoric Archaeology - Roy, Babul (Hukay; Vol 17)
Microlithic sites that were recently discovered in Mandla can contribute to our knowledge regarding the function and continuity of stone tool technology. The question of whether the Mandla example is an isolated case or is an indication of prevalent complex cultural adaptation and regional transformation can still be debated. The latter assumption would challenge the conventional practice of archaeological generalisation. In view of the differential and composite cultural adaptation, it is argued that the practice of chronology construction on typotechnological ground could be a tricky business. In this article, a critical attention is invited on the archaeological practice of generalisation of cultural chronology and the reliability and limitations of typo-technological method – a method still overwhelmingly followed in India with large majority prehistoric archaeological sites found without any contextual/ stratigraphic and/or radiometric dating clues.